Poetics for a Black Revolt - Kanu, Haja Marie (eLyra: Desenvolvimento, 2020)
This essay is written as a response to the compounded crises of police brutality and the Covid-19 pandemic, in the context of the Black Lives Matter movement reignited by the death of George Floyd in 2020. It aims to show how anti-blackness and capitalism are the common denominators contributing to mass death in both crises. The essay explores the possibilities for poetry as radical practice, particularly the work of Black women poets such as Audre Lorde, Ericka Huggins and Warsan Shire. What becomes evident is the centrality of the Black body in reimagining the future, despite its historical emergence from the slave body. I argue that we must return to and reaffirm the bodies that Judith Butler calls abject within theory and poetics, in order to better protect the lives that inhabit them.